Complex Networks & Their Applications VI Proceedings of Complex Networks 2017 (The Sixth International Conference on Complex Networks and Their Applications) - Cherifi, Chantal; Cherifi, Hocine; Karsai, Márton; Musolesi, Mirco (Studies in Computational Intelligence,, 2018)
This book highlights cutting-edge research in the field of network science, offering scientists, researchers, students and practitioners a unique update on the latest advances in theory and a multitude of applications. It presents the peer-reviewed proceedings of the VI International Conference on Complex Networks and their Applications (COMPLEX NETWORKS 2017), which took place in Lyon on November 29 - December 1, 2017. The carefully selected papers cover a wide range of theoretical topics such as network models and measures; community structure, network dynamics; diffusion, epidemics and spreading processes; resilience and control as well as all the main network applications, including social and political networks; networks in finance and economics; biological and ecological networks and technological networks.